2015
DOI: 10.1080/00380768.2015.1041862
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from rice straw burning and straw-mushroom cultivation in a triple rice cropping system in the Mekong Delta

Abstract: The Mekong Delta produces 21 Mt of rough rice (Oryza sativa L.) and an estimated 24 Mt of straw (dry weight) annually. Approximately one fourth of the straw is burned on the field, which is a common practice in intensive rice cultivation systems in this region because there is limited time to prepare the field for the next crop. The spread of intensive rice production in the Delta may increase the total biomass of burning crop residues, significantly impacting greenhouse gas (GHG) emissions in Vietnam. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 28 publications
(32 reference statements)
1
35
0
1
Order By: Relevance
“…of rice straw annually. The spread of these crop residues in this area can increase CS and SOM, significantly reducing GHG emissions [66]. Crop residue decomposition acceleration can enhance the SOM [67].…”
Section: Soil Fertility Managementmentioning
confidence: 99%
“…of rice straw annually. The spread of these crop residues in this area can increase CS and SOM, significantly reducing GHG emissions [66]. Crop residue decomposition acceleration can enhance the SOM [67].…”
Section: Soil Fertility Managementmentioning
confidence: 99%
“…There is only one published study available on methane emissions in the MRD, but that focuses on straw burning and mushroom production (Arai et al 2015), so the reported values cannot be taken as a reference for our study. Moreover, there are few studies from other deltas of Vietnam available such as the Red River Delta in North Vietnam (Pandey Nguyen et al 2014;Nguyen et al 2016;Vu et al 2015;Tariq et al 2017) and the Vu Gia/Thu Bon delta in Central Vietnam (Tirol-Padre et al 2017) which reported values ranging from 104 to 696 kg CH 4 ha −1 per season.…”
Section: Zonal Differentiation and Seasonal Patternsmentioning
confidence: 99%
“…The deltaic rice production systems are characterized by very specific hydrological conditions as compared to other rice-growing environments (Wassmann et al 2009), so that the application of default emission factors may be erroneous. However, there are only few studies published on methane emissions of rice grown in such environments (Pandey Nguyen et al 2014;Arai et al 2015;Vu et al 2015;Nguyen et al 2016;Tariq et al 2017;Tirol-Padre et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The alluvial soils of the MRD also have similar fertility characteristics of alluvial soil in the RRD; however, the texture is heavier (Le and Pham 2015). Although several field experiments for paddy CH 4 emission have been conducted in the RRD, Northern Vietnam (Vu et al 2015;Pandey et al 2014) and the MRD, Southern Vietnam (Arai et al 2015), the existing dataset is still scarce for Central Vietnam (e.g., Tirol-Padre et al 2017).…”
Section: Introductionmentioning
confidence: 99%